Respuesta :
Answer:
The required expression is [tex]-c^2(3c-2)=-3c^3+2c^2[/tex]
Step-by-step explanation:
Given : Expression [tex]-c^2(3c-2)[/tex]
To find : Multiply the given expression?
Solution :
Step 1 - Write the expression
[tex]-c^2(3c-2)[/tex]
Step 2 - Apply the distributive property [tex]a(b+c)=ac+bc[/tex]
[tex]=-c^2\times 3c-2\times(-c^2)[/tex]
Step 3- Multiply
[tex]=-3c^3+2c^2[/tex]
Therefore, The required expression is [tex]-c^2(3c-2)=-3c^3+2c^2[/tex]
The result of applying distributive property to -c^2(3c - 2) is -3c^3 +2c^2
The expression is given as:
[tex]-c^2(3c - 2)[/tex]
To apply distributive property, is to expand the expression.
So, we have:
[tex]-c^2(3c - 2) = -c^2*3c +c^2* 2[/tex]
Evaluate the products
[tex]-c^2(3c - 2) = -3c^3 +2c^2[/tex]
Hence, the result of applying distributive property to -c^2(3c - 2) is -3c^3 +2c^2
Read more about distributive properties at:
https://brainly.com/question/2807928